Promoting veganism. The effects of film propaganda. - Dontsova, Ekaterina (2021)
The topic of propaganda in cinematography has been explored by many because of the opportunity movies have to influence peoples’ opinions. Particularly effective at this task are documentaries. Vegan propaganda seems to be underrepresented in studies conducted to determine its influence. The theoretical part of the thesis defines propaganda tools according to the Institute for Propaganda Analysis. Moreover, in the fourth and fifth chapters, I look into the devices used to influence the audiences of Nazi and Soviet propaganda. After defining the most effective tools, in the practical part, I analyse propaganda traits in the recent successful film “Seaspiracy”, which brings up the topic of sustainable fishing. Moreover, I focus on the filmmaking techniques and expressive means of cinematography that helped to convey the message of the film. This part of the thesis continues with quantitative research, particularly survey research. Its goal is to understand whether the audience of the film was able to recognise propaganda in the movie. The thesis offers empirical data, that show the level of the effectiveness of propaganda. The result of the research shows that out of 30 people who ate fish before watching the movie, 21 did consider changing their eating habits.